A low-profile conical beam loop antenna with an electromagnetically coupled feed system. - Nakano, H. (IEEE Transactions on antennas and propagation)
The radiation characteristics of a low-profile loop antenna are evaluated using the method of moments (MoM). The loop having a circumference of approximately two wavelengths is electromagnetically coupled to a bent Feed line and radiates a circularly polarized conical beam. The frequency bandwidth for a 3-dB axial ratio criterion is calculated to be approximately 0.5% for an antenna height of h=0.064 wavelengths. Over the same bandwidth, the input impedance is approximately 50 ohms and the gain is approximately 7 dB